Estudo das propriedades psicométricas do inventário de estilos parentais de young no Brasil - Valentini, Felipe (2009)
Parenting styles concern overall interaction characteristics between parents and children. To assess them, it is important to build and adapt valid and reliable instruments. The main objectives of this dissertation were to translate, adapt and evaluate the psychometric properties of the Young Parenting Inventory (YPI) for the Brazilian context, as seek associations between the YPI and Familiogram Test (FG). In current study, YPI was adapted to Portuguese by backtranslation method. Content analyses were made by five judges. 920 high school and college students (543 females), whose ages were between 14 and 69 years (M = 21.3, SD = 6.1), filled out the research instruments. Data were collected in Natal, Petrolina and Brasilia cities and Porto Alegre metropolitan region. The results confirmed the existence of five factors. Final version of the YPI was composed by 49 items. Exploratory factorial analysis (principal components) were conducted using oblimin rotation. Five factors extracted explained 45.12% of the maternal scale variance and 47.59% of paternal scale. Each factor explained, at least, 3% of the variance and showed Eigenvalue over than 1.5. All items have factorial loadings values above 0.3. The confirmatory factorial analysis has showed fit statistics reasonably adequate: for maternal scale,  ² [1114] = 4636.38, p < 0.001,  ² / df = 4.16, with GFI = 0.83, AGFI = 0.81 and RMSEA = 0.06; for paternal scale,  ² [1114] = 5133.69 p < 0.001,  ² / df = 4.61, with GFI = 0.81, AGFI = 0.79 and RMSEA = 0,06. Thus, final instrument was composed by the following factors: (I) Disconnection and Rejection ( = 0.89 and 0.90), (II) Affectivity and Emotional Stability ( = 0.85 and 0.88); (III) Overvigilance and Other Directedness ( = 0.83 and 0.85), (IV) Overprotection and Impaired Autonomy ( = 0.78 and 0.79) and (V) Impaired Limits ( = 0.66 and 0.71). Finally, relations between the YPI and FG were assessed. Pearson's correlations between the YPI and FG showed moderated associations, particularly between the factors Affectivity (YPI) and Affection (FG) (r = 0.69 and 0.7 for maternal and paternal scale, respectively); and the factors Disconnection and Rejection (YPI) and Conflict (FG) (r = 0.59 and 0.58). The regression models indicated that over than 40% of variance of factors of FG can be predicted by factors of YPI. Beta coefficients for Affection-Affectivity relation were 0.67 (maternal scale) and 0.53 (paternal scale); for Disconnection-Conflict relation were 0.31 (maternal scale) and 0.44 (paternal scale). We conclude the YPI has adequate psychometric parameters and can be used in future research in this area. However, adjustments in the structure of the YPI were made. Moreover, it is suggested further studies to consider other samples and variables, increasing the knowing of parenting styles and the Young‟s theory in the Brazilian context